Pengaruh Teknologi Informasi Dan Karakteristik Sistem Akuntansi Manajemen Terhadap Kinerja Manajerial Dengan Kompetensi Manajerial Sebagai Variabel Moderasi Pada Kepala Unit Kantor PT. PNM Mekaar Regional Makassar 1 - Nurmini Andryani B; Masdar Masud; Julianty Sidik Tjan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine and analyze the influence of information technology and management accounting system characteristics on managerial performance, with managerial competence as a moderating variable. This study used a quantitative method with a survey approach involving 42 respondents, consisting of all unit heads at PT PNM Mekaar Regional Makassar 1. Data analysis was performed using Partial Least Squares (PLS) Regression, as this model is able to address multicollinearity issues and limited sample size. The results indicate that information technology and management accounting system characteristics have a positive and significant effect on managerial performance. Furthermore, managerial competence also directly influences managerial performance and is proven to moderate the influence of both information technology and management accounting system characteristics on managerial performance. This means that the higher the managerial competence of unit heads, the stronger the influence of technology and accounting systems on improving their performance. The implications of this research demonstrate the importance of developing managerial competence and optimizing the integrated use of information technology and management accounting systems to improve the performance effectiveness of unit heads at PT PNM Mekaar